Effect Of Various Cleaning Agent On Microfiltration Membrane Fouled By Oil Emulsion - Muhamad, Aisyah (Universiti Sains Malaysia, 2018)
Cleaning strategies of microfiltration membrane fouled during separation of oil emulsion have been thoroughly study in this research work. There is various cleaning medium evaluated based on their cleaning efficiencies including alkali, acid, chemical surfactant and bio surfactant rhamnolipid. Analysis of flux behaviour indicates possibly cake formation is a dominant fouling model. This model is effectively fitted to the experimental flux behaviour . The developed cake is responsible for severe fouling and decrease membrane flux. Cleaning efficiency demonstrated by determination of flux restored ratio (FRR) and flux recovery (FR). Sodium dodecyl sulphate (SDS) obtain highest flux restored recovery (FRR) of 28.38% and flux recovery (FR) of 24.11% respectively. Cleaning by SDS largely remove the foulant on the membrane. Influence of operating condition of cleaning the MF membrane were made such as concentration, cleaning time, cleaning trans membrane pressure and method of cleaning. SDS with concentration of 0.10 M SDS selected for futher investigation on the optimum condition for cleaning medium. SDS demonstrated to be effective in cleaning for 30 minutes operation of cleaning time by employing technique of forward flushing at trans membrane pressure of 0.1 MPa.